Spectroscopic Characterization of PEG-DNA Biocomplexes by FTIR - Nagib A. Elmarzugi, Terin Adali, Ali M. Bentaleb, Eseldin I. Keleb, Aref T. Mohamed, Amel M. Hamza (Journal of Applied Pharmaceutical Science, 2014)
Understanding the mode involved in the binding of certain molecules to DNA is of prime importance, and PEG offers wide-ranging applications in biological, medical and pharmaceutical contexts. FTIR spectroscopy has been used to characterize how the formed biocomplexes bind or dissociate to/from each other between PEG400-ctDNA under different conditions. Characterization and investigation of the effect of incubation time on PEG400-ctDNA biocomplexes formation were studied through spectroscopic technique FTIR. The influence of time duration and incubation on intermolecular interaction was analysed at three different selected times (Zero, 1hr, and 48 hrs.) at 1:1 PEG400-ctDNA monomer to nucleotide ratio. The experiment was carried out at room temperature 22 ºC, with prior vortex stirrer of biocomplex for 10 min to improve homogeneity of sample. The results showed that the binding reaction of PEG400-ctDNA proceeds rapidly through DNA base pairs and phosphate DNA backbone, and complexation was reached after a maximum 1hr after mixing PEG400 and ctDNA at 1:1 ratio. FTIR spectroscopy results suggest that PEG400 binds with ctDNA by weak to moderate biocomplexes formation, with both hydrophilic and hydrophobic contact through DNA base pairs, with minor binding preference towards phosphate backbone of DNA helix. The mode of interaction most likely referred to an interaction through outside groove binding or electrostatic binding modes. FTIR highlighted the significant effect of incubation time on the stable biocomplexes of non-ionic PEG400 and ctDNA. Moreover, FTIR spectroscopy technique was rapid, showed good stability, and is a valuable tool for studying the biological properties of biocomplexes of PEG400 and ctDNA.
Keywords: PEG400, Calf thymus DNA, FTIR, Biocomplexes, Incubation time, binding.